Reforms of the Administrative-procedural Legislation in Serbia - Milkov, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Serbia as a member of the Kingdom of Yugoslavia had the Law on General Administrative Procedure since 1930, only five years after Austria who was the first country in the world which codified administrative procedure 1925. ﻿﻿This Law was applicable till the end of the World War II. A socialist Yugoslavia adopted its first law on general administrative procedure in 1956. ﻿This Law was amended several times, but never substantial. ﻿Instead, they carried out minor changes and amendments to this Act, mostly concerning only terminology.